Psychometric evaluation of the tourist behavior scale: Insights from Peruvian tourists - Jose Joel Cruz-Tarrillo (Innovative Marketing)
Tourism has become one of the most important activities, contributing significantly to national development. That is why understanding tourist behavior is essential but also very complex, as each tourist manifests different motivations when making a tourist trip. The objective of this research has been to evaluate the psychometric perspectives and invariance of the tourist behavior scale in the Peruvian context. The study focuses on the positivist paradigm with a quantitative, non-experimental, cross-sectional methodological perspective. The data collection was carried out with a non-probabilistic sampling by convenience to tourists who visited the tourist destinations of the Peruvian jungle as Laguna Azul, Ahuashiyacu, Alto Mayo, Lamas, obtaining as a sample 778 valid responses. The results show a two-dimensional scale (intention to revisit α=0.819; intention to recommend α=0.882) with adequate internal consistency indices. On the other hand, the convergent and discriminant validation indices (CR=0.825; 0.850; AVE=0.612; 0.654) guarantee a valid and representative scale. Furthermore, the scale’s factor structure was shown to be strictly invariant in the groups of men and women, which suggests that both genders share a similar conception of the tourist behavior scale and have a similar interpretation of the items of each factor. In conclusion, the factorial invariance indicates that the scale can be reliably applied in mixed samples (men and women), guaranteeing its validity and reliability in the measurement of tourism behavior. Furthermore, it is suggested to consider its use in future research and in the evaluation of tourism marketing strategies, since it is an accurate and robust tool for understanding tourists’ intentions.